Hemodynamic Responses to Low-Load Blood Flow Restriction and Unrestricted High-Load Resistance Exercise in Older Women - Scott, Brendan R.; Peiffer, Jeremiah J.; Thomas, Hannah J.; Marston, Kieran J.; Hill, Keith D. (Frontiers in Physiology, 2018)
Introduction: Blood flow restriction (BFR) during low-load resistance exercise increases muscle size similarly to high-load training, and may be an alternative to lifting heavy weights for older people at risk of sarcopenia. However, few studies have addressed the safety of such exercise in older people, or whether this is impacted by the actual exercises performed during training. This study aimed to compare the acute hemodynamic and perceptual responses during low-load BFR exercise to unrestricted low-load and high-load exercise in older women, and to determine whether these responses depend on the type of exercise performed. Methods: Fifteen older women (63-75 yr) were assessed for maximal strength (1RM) in the leg press and leg extension. Participants then completed three protocols using these exercises in a randomized order: 1) low-load exercise (LL); 2) low-load exercise with BFR (LLBFR), and; 3) high-load exercise (HL). Blood pressure was assessed at baseline and after each set, and impedance cardiography measured cardiovascular function during trials. Rating of perceived exertion and muscle soreness scores were obtained throughout trials. Results: Baseline hemodynamic values were consistent between trials. Systolic, diastolic and mean arterial pressures were higher in LLBFR compared with HL and LL (p ≤ 0.021). The LL condition resulted in lower heart rate (p ≤ 0.002) and rate-pressure product (p ≤ 0.011) responses compared with LLBFR and HL. The leg press generally conferred greater hemodynamic and perceptual demands than the leg extension for all conditions (p ≤ 0.002). Rating of perceived exertion was lower during LL compared with LLBFR and HL (p ≤ 0.008), and there were no between-condition differences in perceived muscle soreness. Conclusions: The blood pressure data indicate that LLBFR causes greater stress on the vasculature than LL and HL exercise, and that the leg press was generally more demanding than the leg extension. While additional cardiovascular measures were similar between LLBFR and HL conditions, caution should be advised when prescribing BFR exercise for individuals with compromised cardiac or vascular function. Nevertheless, LLBFR and HL exercise were perceived similarly, indicating that BFR training may be viable for healthy older people.